The Status of Customary Tenants in Relation to Land Held by Him: An Overview of Customary Law - Otu, Michael Takim; Edet, Joseph (International Journal of Law and Society, 2023)
The article seeks to examine the effects of the Land Use Act of 1978 on the customary system of land holding in Nigeria. Since the birth of the Act, the problem facing our courts, ordinary people and lawyers is determining the actual position of customary tenants under the system of property rights introduced by the Law. The empirical legal research method used in this study is a type of qualitative research. This method focuses on cases in the community using legal studies, while the scope of this research is the Land Use Act 1978 against the customary land tenure system in Nigeria. The results of the discussion made it clear that the Laws on Land Use and Customary Land Owners have much in common. As such, the controversies generated by these issues continue to defy consensus among our academic "egg heads" as well as learned judges in our courts. Indeed, many court decisions appear to indicate that the courts have not settled the controversy on this issue. As a result, the judicial confusion for Nigerian means of conveyance continues to this day.